2005
DOI: 10.1159/000085021
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Screening for Congenital Adrenal Hyperplasia in North-Eastern Italy: A Report Three Years into the Program

Abstract: Aims: To evaluate the incidence of congenital adrenal hyperplasia (CAH) in the Northern Italian population and the efficiency of the North-Eastern Italy screening program. To adjust cut-off levels for 17-hydroxyprogesterone (17-OHP) in relation to gestational age and birth weight, comparing the benefits in terms of reduction of recall rates with the two approaches and ultimately choosing the better of the two. Subjects and Methods: Since September 2001, blood samples from neonates born in North-Eastern Italy h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
0
13
0
1
Order By: Relevance
“…We used the Spearman rank correlation test to analyze the correlations between the PPV and gestational age and between the 17αhydroxyprogesterone level and CYP21A2 genotype. The Pearson product moment correlation test was used to correlate the reported sensitivity and years of follow-up in previous studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…We used the Spearman rank correlation test to analyze the correlations between the PPV and gestational age and between the 17αhydroxyprogesterone level and CYP21A2 genotype. The Pearson product moment correlation test was used to correlate the reported sensitivity and years of follow-up in previous studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that several cases of the NC form showed elevated 17-OHP levels and were identified by neonatal screening (2, 3, 23, 24). Identification of this form would require a lower cutoff value and entail a significant increase in false positive recalls.…”
Section: Discussionmentioning
confidence: 99%
“…The unrecognized and thus untreated disease may lead to life-threatening SW crisis in the newborn period (2). Neonatal screening for classical 21-OHD, which is now routinely performed in most western countries, has significantly reduced the number of SW crises in neonates and thereby mortality rates during infancy (2,3,4,5). However, patients with classical CAH are at risk of lifethreatening adrenal crisis (AC) during their entire life (6,7).…”
Section: Introductionmentioning
confidence: 99%